KNOWLEDGE AND PERCEPTION ON AUGMENTED REALITY AND VIRTUAL REALITY IN DENTISTRY AMONG DENTAL PRACTITIONERS: AN ORIGINAL RESEARCH (Journal of Pharmaceutical Negative Results, 2022)
Aim: The purpose of the present research was to assess the knowledge amongst dental practitioners about the concept of augmented reality as well as virtual reality in dentistry.Methodology: Online survey was conducted amongst 60 dental practitioners to assess their knowledge as well as implementation of Virtual reality-based technology (VBRT)/Augmented Reality (AR) in their clinical practice using google forms. The Chi square test was used to test differences between groups. Values of p<0.05 were considered statistically significant.Results: Dental practitioners have overall positive attitudes towards VRBT but very few have used VRBT in education and practice. The majority of respondents plan to use VRBT in their future clinical practice and believe that those technologies will be widely adopted by dental practices within 22 years.Conclusion: Learning about VRBT/AR and using them as part of undergraduate and continued education programmes could affect dental practitioners’ willingness to implement new technologies and enhance critical assessment of new trends in dentistry.